Pemberdayaan Ekonomi bagi Ibu-Ibu Rusun Penjaringan Sari Surabaya - Mega Arisia Dewi; Sasi Agustin; Kasrowi Akhmad (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The COVID-19 pandemic has caused the country's economy to experience a negative trend. This is indicated by the decline in the number of people's income, especially MSMEs and small traders. For economic efforts, the Government is trying to move MSMEs back, among others, through Economic Empowerment for Flat Women, especially in the city of Surabaya. The condominium women empowerment program is based on Surabaya Mayor Regulation No. 55/2016 on the regulation, control, empowerment of women and child protection in the city of Surabaya, which provides various kinds of knowledge and knowledge in exploring self-potential that can be used to increase the income of women in flats. The women of flats are vying to increase their income in the midst of the covid pandemic. The women in the flats do not give up and continue to work, producing something useful and generating selling points for their lives and for others. The movement of their small business is not in line with a good production strategy. Therefore, STIESIA Surabaya Lecturers share their knowledge by providing production strategy and business ethics training, which is expected to provide useful values ??that can be used to develop the business of the women in the flats